High- and low-affinity single-peptide/MHC ligands have distinct effects on the development of mucosal CD8alphaalpha and CD8alphabeta T lymphocytes. - O'FARRELLY, CLIONA (My University, 1999)
In this study, we compared the influence of two peptides on the selection of CD8alphaalpha and CD8alphabeta intraepithelial lymphocytes (IELs) of the intestine, which develop by a unique and partially thymus-independent process. Mice were used in which all T cells carried one transgenic T cell antigen receptor (TCR) (F5), and in which only well defined transgenic peptides were presented by H-2Db. The first peptide, for which the F5 TCR has a high affinity, derives from the influenza virus nucleoprotein (NP68). The second peptide, NP34, is an antagonistic variant of NP68 and is recognized by the F5 TCR with low affinity. To avoid presentation of endogenous peptides or production of T cells carrying alternative TCRs, F5 TCR transgenic mice were generated that were deficient for Tap-1 and Rag-1. In these mice, no CD3(+)CD8(+) cells were found in lymph nodes, spleen, or intestine. Introduction of transgenes encoding either NP34 or NP68 along with an endoplasmic reticulum signal sequence enabled Tap-1-independent expression of each peptide in these mice. Positive selection of F5TCR+CD8(+) thymocytes was not rescued by these transgenic peptides. However, the high-affinity NP68 peptide induced maturation of CD8alphaalpha IEL, whereas the low-affinity NP34 peptide stimulated development of both CD8alphabeta and CD8alphaalpha IEL, but in smaller numbers. When both peptides were present, CD8alphabeta T cells failed to develop and the number of CD8alphaalpha IELs was lower than in mice carrying the NP68 transgene alone. These data demonstrate that single ligands with a high or low affinity for TCR are capable of inducing or inhibiting the maturation of alternative subsets of IELs.
PUBLISHED
Keywords: CD8alphaalpha and CD8alphabeta intraepithelial lymphocytes (IELs); CD8alphaalpha and CD8alphabeta intraepithelial lymphocytes (IELs); Immunology, Inflammation & Infection